The role of brain dopaminergic system in forming of EEG biofeedback sessions effects - Yu. O. Fokina; A. M. Kulichenko; V. B. Pavlenko (Бюллетень сибирской медицины)
It was shown on awake cats that activity of dopaminergic neurons of the ventral tegmentum was significantly increased during EEG biofeedback sessions directed on increasing of occipital area alpha- and teta-rhythms spectral powers (SP) relation or sessions wich were directed on increasing of frontal area beta- and teta-rhythms SP relation.